The Number, Weight and Structure of Shortened Branches Formed During Pruning in Intensive Apple Orchards - Yunusov, Rustam (Центр Научных Публикаций (buxdu.uz), 2022)
This article shows the effect of the rejuvenating pruning method with a 3-4 year cycle of replacing overgrown branches, leaving 4-8, 8-12 and 12-16 fruit buds. It has been established that in overgrowing branches, with the degree of rejuvenating pruning left, the mass, number and structure of branches increase accordingly.